Diaphragmatic myotrauma: a mediator of prolonged ventilation and poor patient outcomes in acute respiratory failure. Issue 1 (January 2019) - Goligher, Ewan C; Brochard, Laurent J; Reid, W Darlene; Fan, Eddy; Saarela, Olli; Slutsky, Arthur S; Kavanagh, Brian P; Rubenfeld, Gordon D; Ferguson, Niall D
Summary: Several mechanisms of diaphragm muscle injury (myotrauma) can result in ventilator-induced diaphragm dysfunction, including ventilator over-assistance, under-assistance, eccentric contractions, and end-expiratory shortening. In this Personal View, we summarise the evidence for the clinical relevance of these mechanisms, and present new data based on mediation analysis supporting the hypothesis that myotrauma due to ventilator over-assistance and under-assistance contribute, in part, to the effect of mechanical ventilation on clinical outcomes. The concept of diaphragmatic myotrauma has important implications for research and clinical practice.